Analysis of Problems and Strategies in College French Writing - Li, Ziyan (Journal of Educational Research and Policies, 2024)
This article mainly discusses the problems existing in College French writing and the corresponding strategies. Writing is an important skill that students must master, but there are three main problems in College French teaching: limited vocabulary leading to frequent pragmatic errors; significant negative transfer from native language; and difficulties in closely adhering to the essay topic or the beginning of the paragraph. To address these issues, teachers adopt a variety of targeted teaching strategies, including task-based language teaching, intercultural communication teaching methods, and process writing approaches. The implementation of these strategies has significantly improved the students’ College French writing skills.